Where will the cat cross the road? Comparing camera and GPS-based models for identifying wildlife corridors - Read Barbee; L. Mark Elbroch; Kimberly Sager-Fradkin; Kristen Phillips; Dylan Bergman; Bethany Ackerman; Shannon Murphie; Andrew Stratton; Caitlin Kupar; Cassandra Sullivan; Glen Kalisz; Sarah N. Sells; et al. (Biological Conservation, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Stock Identity of Stranded Tamanend's Bottlenose Dolphins ( Tursiops erebennus ) With Evidence of Fisheries Interaction in Virginia, North Carolina, and South Carolina, 1996–2019 - Kim W. Urian; Susan G. Barco; Karen L. Clark; Alex M. Costidis; Paul Doshkov; Marina Piscitelli‐Doshkov; Alexandra L. Epple; Tiffany F. Keenan; William A. McLellan; Wayne E. McFee; D. Ann Pabst; Keith A. Rittmaster; et al. (Marine Mammal Science, 2026)
The complex population structure of Tamanend's bottlenose dolphins ( Tursiops erebennus ) along the U.S. Mid‐Atlantic coast complicates assessment of their bycatch. To improve our understanding of the stock identity of individual dolphins taken as bycatch in this region, we compared images of the dorsal fins of bottlenose dolphins that stranded with evidence of fishery interactions (FI+) to the Mid‐Atlantic Bottlenose Dolphin Catalog (MABDC). We obtained stranding data from NOAA Fisheries for 715 FI+ bottlenose dolphins from Virginia (VA), North Carolina (NC), and South Carolina (SC) from 1996 to 2019; approximately two thirds of these records included dorsal fin images. For records for which images were available, we applied restrictive criteria for image quality and dorsal fin distinctiveness and compared the remaining 145 distinctive FI+ individuals to the MABDC. We matched 18 dolphins to regional catalogs and assigned stock identity to 13 of the matches; two were from migratory coastal stocks and 11 were from small estuarine stocks in NC and SC. Our analysis demonstrates how the risk of bycatch varies across bottlenose dolphin stocks along the Mid‐Atlantic coast, provides an important feedback information loop to stranding responders and researchers studying dolphins in the field, and informs conservation efforts to address bycatch of bottlenose dolphins in this region.

In Memoriam Timothy B. Werner 1962–2025 - Scott Kraus; Michelle Cho; Les Kaufman; Jeremy J. Kiszka; Eric Newton; Andrew J. Read; Claire Werner; Madeleine Werner (Marine Mammal Science, 2026)

What controls current and future background vulnerability of rivers to eutrophication and pathogens? - Michael Hutchins; Emma Gardner; Lisa Gechelle; Andrew Johnson; Yueming Qu; Dinara Sadykova; Michael Bowes; Daniel Read; Claire Robertson (Journal of Hydrology, 2026)

Presence and characteristics of plastics and microplastics on the seabed of the western English Channel - Faye Read; Andrew Turner (Marine Pollution Bulletin, 2026)

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

Complex population structure revealed using genomic data from Tamanend’s bottlenose dolphins (Tursiops erebennus) - Nicole L. Vollmer; Lynsey A. Wilcox Talbot; Antoinette M. Gorgone; Aleta Hohn; Andrew J. Read; Eric S. Zolman; Patricia E. Rosel (Marine Biology, 2025)
In the waters of North Carolina, on the United States east coast, Tamanend’s bottlenose dolphin ( Tursiops erebennus ) is managed as four stocks, differentiated largely based on photo-identification and satellite telemetry data. Two of the stocks reside primarily within estuarine habitats throughout the year, and two others inhabit coastal waters and make broad scale, migratory movements. The spatio-temporal overlap of these stocks in North Carolina varies seasonally, creating a complicated scenario in which stock boundaries are difficult to identify, and the demographic independence among groups is not well understood. Furthermore, incidental mortality and serious injury of dolphins occurs in several North Carolina fisheries, but the spatio-temporal overlap of the four stocks makes it difficult to assign mortalities and characterize their impact on each stock. To investigate population structure in this complex environment, we obtained biopsy samples from Tamanend’s bottlenose dolphins, and utilized next-generation molecular sequencing to produce a data set of over 6,000 single nucleotide polymorphism markers. Cluster and migration analyses supported the presence of four demographically independent populations. However, the distributions of these populations do not align well with the currently delineated stocks. Instead, our analyses support the existence of three populations in estuarine waters of North Carolina and one inhabiting coastal waters. An improved understanding of the underlying population structure of Tamanend’s bottlenose dolphins in these waters will provide a better characterization of stock distribution and support more accurate assignment of mortality, which is necessary for successful conservation and management of this species.

Wastewater surveillance of SARS-CoV-2 and influenza in a dynamic university community: understanding how wastewater measurements correspond to reported cases - Matthew J. Jones; Rukayya Ibrahim; Shirley Clark; Yolanda M. Brooks; Heather E. Preisendanz; Thomas L. Richard; Andrew F. Read; Courtney J. Robinson; Samina Noorali; Michael J. Shreve; Nina L. Dennington; Justin D. Silverman; et al. (Science of The Total Environment, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Overwintering humpback whales adapt foraging strategies to shallow water environments at the mouth of the Chesapeake Bay, Virginia, USA - Jeanne M. Shearer; Heather J. Foley; Zachary T. Swaim; Vincent M. Janik; Andrew J. Read (Marine Mammal Science, 2025)
Some humpback whales from the Northwestern Atlantic population forgo migration to the Caribbean, spending winter months feeding along the U.S. mid‐Atlantic coast. We studied the foraging behavior of these whales at the mouth of the Chesapeake Bay, Virginia during winter from 2017 to 2022. While shipping channels here reach depths of up to 30 m, most of the area is 11–15 m deep. This shallow‐water environment poses physical constraints on classical humpback whale feeding modes. We deployed 20 digital acoustic tags (DTAGs) on humpback whales and identified foraging lunges from accelerometer data, detecting 788 lunges from 10 animals. Tagged whales averaged a single lunge per dive, lunging primarily in a horizontal orientation, with limited maneuvering compared to other study sites. Our results indicate that some elements of humpback whale foraging behavior are conserved across environments, but that the shallow depths in our study area constrain how animals are able to feed. The relatively high lunge rates we observed suggest this area is an important foraging ground. However, foraging in shipping channels increases the risk of ship strikes, which frequently occur in this area.

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

Song fragments recorded on a tagged juvenile humpback whale ( Megaptera novaeangliae ) on a winter feeding ground at the mouth of the Chesapeake Bay, Virginia, USA - Dana L. Adcock; Jeanne M. Shearer; Heather J. Foley; Zach T. Swaim; Andrew J. Read (Marine Mammal Science, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Fate and behaviour of Microplastics (> 25µm) within the water distribution network, from water treatment works to service reservoirs and customer taps - Gbotemi A. Adediran; Ruairidh Cox; Monika D. Jürgens; Elise Morel; Richard Cross; Heather Carter; M. Glória Pereira; Daniel S. Read; Andrew C. Johnson (Water Research, 2024)

Influence of sample size, model selection, and land use on prediction accuracy of soil properties - Samira Safaee; Zamir Libohova; Eileen J. Kladivko; Andrew Brown; Edwin Winzeler; Quentin Read; Shams Rahmani; Kabindra Adhikari (Geoderma Regional, 2024)

Preliminary assessment of bacterial antibiotic resistance and Candidatus Liberibacter asiaticus titer in three Florida commercial citrus groves - Marie de Gracia Coquerel; Jieli Wegerif; Andrew McAuley; Quentin D. Read; Nabil Chowdhury; Kwang Cheol Jeong; J. Glenn Morris; Samuel J. Martins; Erica M. Goss; Marina S. Ascunce (Crop Protection, 2023)

Observed trends in scavenging by common bottlenose dolphins ( Tursiops truncatus truncatus ) in for‐hire fisheries in the eastern U.S. Gulf of Mexico - Corie E. Grewal; Jessica R. Powell; Stacey C. Horstman; Nicholas A. Farmer; Oscar Ayala; Andrew J. Read (Marine Mammal Science, 2023)
Interactions between bottlenose dolphin and recreational rod and reel fisheries are a complex issue for resource managers in the United States, which may impact anglers' catch and lead to dangerous situations for scavenging or depredating dolphins. To examine this issue, we analyzed data collected by observers on for‐hire fishing vessels off the eastern U.S. Gulf Coast from 2009 to 2020. A generalized additive model indicated number of anglers, number of discarded fish, proximity to shore, prior scavenging events, type of released fish, and area fished were all significant predictors of scavenging by dolphins. The Florida panhandle had the highest odds of scavenging, while scavenging in the Big Bend and Tampa Bay has increased through time. The Florida panhandle is a well‐known area for illegal feeding of dolphins, suggesting human behavior may be influencing fisheries interactions. Model outputs indicate that dolphins are primarily cuing on fishing activity rather than number of discards, but are more likely to scavenge discards from the family Lutjanidae (snappers), which comprised 40% of observed discards but 80% of scavenging events. This study highlights factors influencing the frequency of dolphin scavenging events, guiding managers and scientists on additional studies and mitigation measures needed to address this issue.

Havens are a pathway, not an endpoint, for species recovery: A response to Woinarski et al. (2023) - John L. Read; Kev Bradley; Iain J. Gordon; Adrian D. Manning; Linda E. Neaves; April E. Reside; Kiarrah J. Smith; Rick Southgate; Adrian F. Wayne; Andrew R. Weeks; Belinda A. Wilson; Katherine E. Moseby (Biological Conservation, 2023)

Initial characterization of a bacterial leaf streak susceptibility gene suggests it encodes a membrane transporter that influences seed nutrition and germination - Nathan J. Scinto-Madonich; Shivranjani Baruah; Sameya Young; Katherine Vignona; Andrew C. Read; Sara C.D. Carpenter; Li Wang; Xinying Shi; Geoffrey Chang; Miguel A. Piñeros; Adam J. Bogdanove (Physiological and Molecular Plant Pathology, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Cetacean bycatch management in regional fisheries management organizations: Current progress, gaps, and looking ahead - Brianna Elliott; Marguerite Tarzia; Andrew J. Read (Frontiers in Marine Science, 2023)
Bycatch is the leading global threat to cetaceans, with at least 300,000 cetaceans estimated to be killed each year in fisheries. Regional fisheries management organizations (RFMOs) are key actors in global fisheries management, including bycatch reduction, but their role in cetacean bycatch management is often overlooked. The primary mandate of RFMOs is to manage fisheries of target stocks, but many of their Convention Agreements call for addressing bycatch of threatened and protected species in their fisheries, including cetaceans. We reviewed 14 RFMOs to understand their current cetacean bycatch management efforts. We developed twenty-five criteria for best practices in cetacean bycatch management to understand efforts made by each RFMO, grouped into five categories: 1) general bycatch governance; 2) observer coverage; 3) quantitative bycatch limits; 4) data analysis and transparency; and 5) mitigation efforts. Collectively, based on our application of these criteria, RFMOs scored highest in “data analysis and transparency” (average=0.74) and lowest in setting “quantitative bycatch limits” (average=0.15). Overall, RFMOs have passed few binding conservation and management measures focused on cetacean bycatch, particularly compared to those addressing the bycatch of seabirds and sea turtles; the few existing measures are primarily focused on bycatch in purse seines. Notwithstanding the United Nations (UN) large-scale drift gillnet ban (46/215) on the high seas, only one RFMO has passed a management measure specifically focused on cetaceans and gillnets, widely recognized as the gear type posing the highest risk to cetaceans. No measure in any RFMO specifically addresses cetacean bycatch in longlines. We provide recommendations to the RFMO community to encourage progress on this critical issue, including leveraging other recent policy developments such as the adoption of the 2021 UN Food and Agriculture Organization Guidelines to prevent and reduce bycatch of marine mammals in capture fisheries and implementation of the U.S. Marine Mammal Protection Act Import Provisions.

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Illegal fisheries, environmental crime, and the conservation of marine resources - Eréndira Aceves‐Bueno; Andrew J. Read; Miguel A. Cisneros‐Mata (Conservation Biology, 2021)
The illegal harvest of marine species within exclusive economic zones can have a strong impact on the function of local ecosystems and livelihoods of coastal communities. The complexity of these problems is often overlooked in the development of solutions, leading to ineffective and sometimes harmful social and environmental outcomes. One‐dimensional, oversimplified perspectives can lead to conservation prescriptions that exacerbate social stressors. This is particularly critical in the case of international illegal trade of endangered, high‐value species, which generate a value chain in which artisanal fishers are the first operational and often the weakest link of an intricate web. We examined 2 illegal fisheries, totoaba ( Totoaba macdonaldi ) and sea cucumber ( Isostichopus badionotus and Holothuria floridana ), in Mexico. Although these are 2 separate and independent fisheries, important ecological (resource condition, fishery impacts at the ecosystem level) and social (governance, markets) similarities improve understanding of their complexity. Our findings are relevant globally and show the need for interdisciplinary decision‐making groups, community engagement, and the development of demand reduction measures.

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Empty promises: The European Union is failing to protect dolphins and porpoises from fisheries by‐catch - Emer Rogan; Andrew J Read; Per Berggren (Fish and Fisheries, 2021)
By‐catch is the primary global conservation threat to populations of dolphins and porpoises. Despite protection for these protected species under its Habitats Directive, the European Union (EU) has failed to adequately assess and, where necessary, mitigate the by‐catch of small cetaceans. Management authority is diffuse, and the EU has no over‐arching, quantitative conservation objectives. To address this, we recommend that the EU adopt a comprehensive plan to conserve dolphins and porpoises in European waters. This plan should include regular formal assessments of small cetacean populations, including establishment of quantitative management objectives, generation of estimates of abundance and by‐catch mortality, and agreement on biological reference points that will guide management actions to ensure that by‐catch does not exceed sustainable levels.

The Challenges of Managing Depredation and Bycatch of Toothed Whales in Pelagic Longline Fisheries: Two U.S. Case Studies - Joseph E. Fader; Brianna W. Elliott; Andrew J. Read (Frontiers in Marine Science, 2021)
Direct interactions with fisheries are broadly recognized as the leading conservation threat to small cetaceans. In open-ocean environments, one of the primary gear types implicated in these interactions is the pelagic longline. Unlike accidental entanglement in driftnets or deliberate entrapment by purse-seines, interactions between cetaceans and longlines are often driven by attraction of the animals to feed on bait or fish secured on the gear, a behavior known as depredation. Many small and medium-sized delphinid species have learned to exploit such opportunities, leading to economic costs to fisheries and a risk of mortality to the animals from either retaliation by fishermen or hooking or entanglement in fishing gear. Two pelagic longline fisheries in the United States experience depredation and bycatch by odontocete depredators: the Hawai‘i deep-set longline fishery, which is depredated primarily by false killer whales ( Pseudorca crassidens ), and the Atlantic pelagic longline fishery depredated primarily by short-finned pilot whales ( Globicephala macrorhynchus ). These fisheries are among the most intensively documented and managed pelagic longline fisheries in the world, with high levels of observer coverage, and bycatch mitigation measures required to reduce the mortality of seabirds, sea turtles and cetaceans. Both fisheries have active, multi-stakeholder “Take Reduction Teams,” enacted under the U.S. Marine Mammal Protection Act (MMPA), that are tasked to develop measures to reduce the bycatch of cetaceans below statutory reference points. Consequently, these two Teams represent model processes within which to address depredation and bycatch, having access to detailed, high-quality data on the nature and frequency of interactions with cetaceans, meaningful stakeholder involvement, resources to test potential solutions, and the institutional will to improve outcomes. We review how mitigation strategies have been considered, developed, and implemented by both Teams and provide a critical analysis of their effectiveness in addressing these problems. Notably, in the absence of straightforward avoidance or deterrence strategies, both Teams have developed gear and handling strategies that depend critically on comprehensive observer coverage. Lessons offered from these Teams, which have implemented consensus-driven management measures under a statutory framework, provide important insights to managers and scientists addressing other depredation problems.

The impact of temperature at depth on estimates of thermal habitat for short‐finned pilot whales - Stephanie K. Adamczak; William A. McLellan; Andrew J. Read; Christopher L. P. Wolfe; Lesley H. Thorne (Marine Mammal Science, 2021)
Short‐finned pilot whales ( Globicephala macrorhynchus ) experience dramatic changes in temperature during deep dives, but studies of pilot whale habitat use typically rely solely on surface temperature measurements. We quantified vertically integrated thermal habitat for short‐finned pilot whales using a novel metric, degree‐hours, developed using data from digital acoustic recording tags (DTAGs) deployed off Cape Hatteras along with interpolated temperature profiles at depth from the Met Office Hadley Centre EN4 oceanographic data set. We then compared estimates of thermal habitat calculated from surface waters with estimates of vertically integrated thermal habitat calculated using EN4 data collected along the eastern seaboard of the U.S. to understand how available thermal habitat is influenced by seasonal and spatial variability in water temperature. Estimates of vertically integrated thermal habitat were typically lower than estimates produced using surface temperatures, and the difference was greatest at intermediate latitudes and in warmer seasons, where and when there is a high degree of variability between surface and bottom temperatures. Our work highlights the importance of considering temperature at depth to accurately assess the thermal habitat of deep‐diving marine vertebrates, and presents a means of quantifying thermal habitat that will be useful for understanding the thermal ranges of these species.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Beyond counts and averages: Relating geodiversity to dimensions of biodiversity - Quentin D. Read; Phoebe L. Zarnetske; Sydne Record; Kyla M. Dahlin; Jennifer K. Costanza; Andrew O. Finley; Keith D. Gaddis; John M. Grady; Martina L. Hobi; Andrew M. Latimer; Sparkle L. Malone; Scott V. Ollinger; et al. (Global Ecology and Biogeography, 2020)
Aim We may be able to buffer biodiversity against the effects of ongoing climate change by prioritizing the protection of habitat with diverse physical features (high geodiversity) associated with ecological and evolutionary mechanisms that maintain high biodiversity. Nonetheless, the relationships between biodiversity and habitat vary with spatial and biological context. In this study, we compare how well habitat geodiversity (spatial variation in abiotic processes and features) and climate explain biodiversity patterns of birds and trees. We also evaluate the consistency of biodiversity–geodiversity relationships across ecoregions. Location Contiguous USA. Time period 2007–2016. Taxa studied Birds and trees. Methods We quantified geodiversity with remotely sensed data and generated biodiversity maps from the Forest Inventory and Analysis and Breeding Bird Survey datasets. We fitted multivariate regressions to alpha, beta and gamma diversity, accounting for spatial autocorrelation among Nature Conservancy ecoregions and relationships among taxonomic, phylogenetic and functional biodiversity. We fitted models including climate alone (temperature and precipitation), geodiversity alone (topography, soil and geology) and climate plus geodiversity. Results A combination of geodiversity and climate predictor variables fitted most forms of bird and tree biodiversity with Main conclusions Although climatic predictors tended to have larger individual effects than geodiversity, adding geodiversity improved climate‐only models of biodiversity. Geodiversity was correlated with biodiversity more consistently than with climate across ecoregions, but models tended to have a poor fit in ecoregions held out of the training dataset. Patterns of geodiversity could help to prioritize conservation efforts within ecoregions. However, we need to understand the underlying mechanisms more fully before we can build models transferable across ecoregions.

Bioengineering a Future Free of Marine Plastic Waste - Maya U. Sheth; Sarah K. Kwartler; Emma R. Schmaltz; Sarah M. Hoskinson; E. J. Martz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Andrew J. Read; William C. Eward; Jason A. Somarelli (Frontiers in Marine Science, 2019)

Likely annual calving in the vaquita, Phocoena sinus : A new hope? - Barbara L. Taylor; Randall S. Wells; Paula A. Olson; Robert L. Brownell; Frances M. D. Gulland; Andrew J. Read; Francisco J. Valverde‐Esparza; Oscar H. Ortiz‐García; Diego Ruiz‐Sabio; Armando M. Jaramillo‐Legorreta; Edwyna Nieto‐Garcia; Gustavo Cardenas‐Hinojosa; et al. (Marine Mammal Science, 2019)

Towards connecting biodiversity and geodiversity across scales with satellite remote sensing - Phoebe L. Zarnetske; Quentin D. Read; Sydne Record; Keith D. Gaddis; Stephanie Pau; Martina L. Hobi; Sparkle L. Malone; Jennifer Costanza; Kyla M. Dahlin; Andrew M. Latimer; Adam M. Wilson; John M. Grady; et al. (Global Ecology and Biogeography, 2019)
Issue Geodiversity (i.e., the variation in Earth's abiotic processes and features) has strong effects on biodiversity patterns. However, major gaps remain in our understanding of how relationships between biodiversity and geodiversity vary over space and time. Biodiversity data are globally sparse and concentrated in particular regions. In contrast, many forms of geodiversity can be measured continuously across the globe with satellite remote sensing. Satellite remote sensing directly measures environmental variables with grain sizes as small as tens of metres and can therefore elucidate biodiversity–geodiversity relationships across scales. Evidence We show how one important geodiversity variable, elevation, relates to alpha, beta and gamma taxonomic diversity of trees across spatial scales. We use elevation from NASA's Shuttle Radar Topography Mission (SRTM) and c . 16,000 Forest Inventory and Analysis plots to quantify spatial scaling relationships between biodiversity and geodiversity with generalized linear models (for alpha and gamma diversity) and beta regression (for beta diversity) across five spatial grains ranging from 5 to 100 km. We illustrate different relationships depending on the form of diversity; beta and gamma diversity show the strongest relationship with variation in elevation. Conclusion With the onset of climate change, it is more important than ever to examine geodiversity for its potential to foster biodiversity. Widely available satellite remotely sensed geodiversity data offer an important and expanding suite of measurements for understanding and predicting changes in different forms of biodiversity across scales. Interdisciplinary research teams spanning biodiversity, geoscience and remote sensing are well poised to advance understanding of biodiversity–geodiversity relationships across scales and guide the conservation of nature.

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

The prevalence of ectoparasitic barnacles discriminates stocks of Atlantic common bottlenose dolphins ( Tursiops truncatus ) at risk of entanglement in coastal gill net fisheries - Kim W. Urian; Rachel Kaufmann; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Distribution and abundance of beaked whales (Family Ziphiidae) Off Cape Hatteras, North Carolina, U.S.A. - William A. McLellan; Ryan J. McAlarney; Erin W. Cummings; Andrew J. Read; Charles G. M. Paxton; Joel T. Bell; D. Ann Pabst (Marine Mammal Science, 2018)
Beaked whales are vulnerable to the impacts of disturbance from several sources of anthropogenic sound. Here we report the distribution and abundance of beaked whales off Cape Hatteras, North Carolina, U.S.A., an area utilized by the U.S. Navy for training exercises, and of particular interest for seismic geophysical surveys. From May 2011 through November 2015, monthly aerial surveys were conducted at the site. Beaked whales were encountered 74 times ( n = 205 individuals) during these surveys. Ziphius cavirostris , the most commonly encountered species, was observed in every month of the year. Mesoplodon spp. were encountered in ten months of the year. Photographs of adult males with erupted teeth permitted six sightings to be identified conclusively as M. europaeus ; M. mirus was also photographed just outside the study area. Beaked whale surface densities stratified by depth (0.005–0.007/km 2 ) were among the highest reported in the world for small ziphiids. A quantitative comparison of sightings and stranding records suggests that strandings do not accurately reflect the relative abundance of beaked whale species in this area. We conclude that Cape Hatteras, at the convergence of the Labrador Current and Gulf Stream, is a particularly important year‐round habitat for several species of beaked whales.

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously? - Jeroen P. A. Hoekendijk; Jerome Spitz; Andrew J. Read; Mardik F. Leopold; Michael C. Fontaine (Marine Mammal Science, 2018)

Two‐component calls in short‐finned pilot whales ( Globicephala macrorhynchus ) - Nicola Quick; Holly Callahan; Andrew J. Read (Marine Mammal Science, 2018)
Short‐finned pilot whales ( Globicephala macrorhynchus ) have complex vocal repertoires that include calls with two time‐frequency contours known as two‐component calls. We attached digital acoustic recording tags ( DTAG s) to 23 short‐finned pilot whales off Cape Hatteras, North Carolina, and assessed the similarity of two‐component calls within and among tags. Two‐component calls made up

Movements and home ranges of monk seals in the main Hawaiian Islands - Kenady Wilson; Charles Littnan; Andrew J. Read (Marine Mammal Science, 2017)
Hawaiian monk seals ( Neomonachus schauinslandi ) began recolonizing the main Hawaiian Islands ( MHI ) roughly 20 yr ago. The species’ abundance is still declining, but the subpopulation in the MHI is increasing by 6.5% per year. This difference may be due to differences in prey availability or habitat quality between the northwest ( NWHI ) and main Hawaiian Islands, which could be reflected in the movements and behavior of the seals. For example, foraging trip durations may be shorter in areas with higher forage quality. From 2007 to 2014 we deployed GPS phone tags on the islands of Molokai ( n = 7), Kauai ( n = 6), and Oahu ( n = 6) to study movements and dive behavior. Foraging trips typically lasted 0.57 d ( IQR : 0.34–0.83) and seals traveled 18 km ( IQR : 10.2–30.5) per trip. Seals began benthic dives shortly after entering the water, with most dives to depths of 12–32 m. The median 95% and 50% kernel density isopleths for seals in the MHI were 149.2 km 2 and 23.2 km 2 , respectively. The duration and distance of foraging trips in the MHI were shorter than that observed in other studies from the NWHI , suggesting that foraging habitat is currently better in the MHI .

Genomewide investigation of adaptation to harmful algal blooms in common bottlenose dolphins ( Tursiops truncatus ) - Kristina M. Cammen; Thomas F. Schultz; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Molecular Ecology, 2015)
Harmful algal blooms ( HAB s), which can be lethal in marine species and cause illness in humans, are increasing worldwide. In the Gulf of Mexico, HAB s of Karenia brevis produce neurotoxic brevetoxins that cause large‐scale marine mortality events. The long history of such blooms, combined with the potentially severe effects of exposure, may have produced a strong selective pressure for evolved resistance. Advances in next‐generation sequencing, in particular genotyping‐by‐sequencing, greatly enable the genomic study of such adaptation in natural populations. We used restriction site‐associated DNA ( RAD ) sequencing to investigate brevetoxicosis resistance in common bottlenose dolphins ( Tursiops truncatus ). To improve our understanding of the epidemiology and aetiology of brevetoxicosis and the potential for evolved resistance in an upper trophic level predator, we sequenced pools of genomic DNA from dolphins sampled from both coastal and estuarine populations in Florida and during multiple HAB ‐associated mortality events. We sequenced 129 594 RAD loci and analysed 7431 single nucleotide polymorphisms ( SNP s). The allele frequencies of many of these polymorphic loci differed significantly between live and dead dolphins. Some loci associated with survival showed patterns suggesting a common genetic‐based mechanism of resistance to brevetoxins in bottlenose dolphins along the Gulf coast of Florida, but others suggested regionally specific mechanisms of resistance or reflected differences among HAB s. We identified candidate genes that may be the evolutionary target for brevetoxin resistance by searching the dolphin genome for genes adjacent to survival‐associated SNP s.

The effect of anthropogenic arsenic contamination on the earthworm microbiome - Daniel Antony Pass; Andrew John Morgan; Daniel S. Read; Dawn Field; Andrew J. Weightman; Peter Kille (Environmental Microbiology, 2015)
Summary Earthworms are globally distributed and perform essential roles for soil health and microbial structure. We have investigated the effect of an anthropogenic contamination gradient on the bacterial community of the keystone ecological species L umbricus rubellus through utilizing 16 S rRNA pyrosequencing for the first time to establish the microbiome of the host and surrounding soil. The earthworm‐associated microbiome differs from the surrounding environment which appears to be a result of both filtering and stimulation likely linked to the altered environment associated with the gut micro‐habitat (neutral pH , anoxia and increased carbon substrates). We identified a core earthworm community comprising P roteobacteria (∼50%) and A ctinobacteria (∼30%), with lower abundances of B acteroidetes (∼6%) and A cidobacteria (∼3%). In addition to the known earthworm symbiont ( V erminephrobacter sp.), we identified a potential host‐associated G ammaproteobacteria species ( S erratia sp.) that was absent from soil yet observed in most earthworms. Although a distinct bacterial community defines these earthworms, clear family‐ and species‐level modification were observed along an arsenic and iron contamination gradient. Several taxa observed in uncontaminated control microbiomes are suppressed by metal/metalloid field exposure, including eradication of the hereto ubiquitously associated V erminephrobacter symbiont, which raises implications to its functional role in the earthworm microbiome.

From genome-wide to candidate gene: an investigation of variation at the major histocompatibility complex in common bottlenose dolphins exposed to harmful algal blooms - Kristina M. Cammen; Lynsey A. Wilcox; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Immunogenetics, 2015)

Recommendations for photo‐identification methods used in capture‐recapture models with cetaceans - Kim Urian; Antoinette Gorgone; Andrew Read; Brian Balmer; Randall S. Wells; Per Berggren; John Durban; Tomoharu Eguchi; William Rayment; Philip S. Hammond (Marine Mammal Science, 2015)
Capture‐recapture methods are frequently employed to estimate abundance of cetaceans using photographic techniques and a variety of statistical models. However, there are many unresolved issues regarding the selection and manipulation of images that can potentially impose bias on resulting estimates. To examine the potential impact of these issues we circulated a test data set of dorsal fin images from bottlenose dolphins to several independent research groups. Photo‐identification methods were generally similar, but the selection, scoring, and matching of images varied greatly amongst groups. Based on these results we make the following recommendations. Researchers should: (1) determine the degree of marking, or level of distinctiveness, and use images of sufficient quality to recognize animals of that level of distinctiveness; (2) ensure that markings are sufficiently distinct to eliminate the potential for “twins” to occur; (3) stratify data sets by distinctiveness and generate a series of abundance estimates to investigate the influence of including animals of varying degrees of markings; and (4) strive to examine and incorporate variability among analysts into capture‐recapture estimation. In this paper we summarize these potential sources of bias and provide recommendations for best practices for using natural markings in a capture‐recapture framework.

Field assessment of C‐ POD performance in detecting echolocation click trains of bottlenose dolphins ( Tursiops truncatus ) - Bethany L. Roberts; Andrew J. Read (Marine Mammal Science, 2015)
We evaluated the performance of dolphin echolocation detectors (C‐ POD s) in the New River, North Carolina, by ground‐truthing echolocation detections with digital acoustic recordings. We deployed C‐ POD s at three sites for a total of 204 monitoring hours. We also performed detection range trials at two sites where water depths ranged from 1.0 to 4.5 m. We used Detection Positive Minutes ( DPM s), minutes of C‐ POD recordings that contained at least one echolocation click train, to indicate the presence of at least one dolphin. The C‐ POD s performed well in detecting dolphin click trains, although all units performed conservatively by failing to detect some echolocation events and therefore underestimated the true occurrence of dolphins. C‐ POD s reported only a small number of false detections, as indicated by low false positive rates ranging between 1% and 4% for individual units. Overall, C‐ POD s performed with a high accuracy (72%–91%) and detected echolocation at a distance of at least 933 m. We conclude that C‐ POD s hold considerable promise in future monitoring studies of this species, but recommend a careful study design especially in complex, coastal environments.

A quantitative analysis of the response of short‐finned pilot whales, Globicephala macrorhynchus , to biopsy sampling - Danielle D. Crain; Ari S. Friedlaender; Dave W. Johnston; Doug P. Nowacek; Bethany L. Roberts; Kim W. Urian; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2014)

The influence of habitat and time of day on the occurrence of odontocete vocalizations in Onslow Bay, North Carolina - Lynne E. W. Hodge; Joel T. Bell; Anurag Kumar; Andrew J. Read (Marine Mammal Science, 2013)
To determine whether the occurrence and duration of odontocete vocal events varied by depth or time of day in Onslow Bay, North Carolina, we analyzed acoustic data collected by five underwater recorders. These recorders were deployed in July 2008 at three depths: two in shallow (64–73 m), one in medium (236 m), and two in deep (~366 m) water. We found that habitat influenced the occurrence of odontocete vocalizations, with significantly greater daily vocal activity from delphinids on recorders in deeper waters and sperm whale clicks recorded only on the medium and deep recorders. These findings suggest that a greater diversity and occurrence of animals are located in waters beyond the shelf break in this area, a conclusion supported by visual surveys. We also found an increase in the occurrence of delphinid clicks at night on the shallow and deep recorders, likely reflecting nocturnal foraging activity, and a regular nocturnal occurrence of sperm whale clicks on the medium‐depth recorder located near the shelf break, suggesting that one or more sperm whales moved into that area to feed at night. These observations improve our understanding of the occurrence and behavior of odontocetes in this region of the U.S. Atlantic seaboard.

An Introduction to Marine Mammal Biology and Conservation by E. C. M. Parsons - Andrew J. Read (Marine Mammal Science, 2013)

What can be offered to couples at (possibly) increased genetic risk? - Andrew P. Read; Dian Donnai (Journal of Community Genetics, 2012)

Designing criteria suites to identify discrete and networked sites of high value across manifestations of biodiversity - Eric Gilman; Daniel Dunn; Andrew Read; K. David Hyrenbach; Robin Warner (Biodiversity and Conservation, 2011)

Speicher, Antonarakis, Motulsky (eds): Vogel and Motulsky’s human genetics, 4th edn - Andrew Read (Human Genetics, 2010)

Multiple sightings of large groups of Arnoux's beaked whales (Berardius arnouxii) in the Gerlache Strait, Antarctica - Ari S. Friedlaender; Douglas P. Nowacek; David W. Johnston; Andrew J. Read; Reny B. Tyson; Lindsey Peavey; Eletta M. S. Revelli (Marine Mammal Science, 2009)

Where to catch a fish? The influence of foraging tactics on the ecology of bottlenose dolphins ( Tursiops truncatus ) in Florida Bay, Florida - Leigh G. Torres; Andrew J. Read (Marine Mammal Science, 2009)
Observations of bottlenose dolphins ( Tursiops truncatus ) in Florida Bay, Florida, between 2002 and 2005 revealed the use of three distinct foraging tactics. The goal of this study was to identify ecological correlates with tactic use and describe the impact of foraging specializations on the overall habitat use and distribution patterns of this dolphin population. Foraging tactics showed strong association with contrasting environmental characteristics, primarily depth. Locations of two of these tactic groups were spatially repulsed. Analyses of sighting histories of individual dolphins observed at foraging events determined that dolphins which employed one tactic never employed the other, and vice versa . Although bottlenose dolphins have plastic foraging behaviors, dolphins in Florida Bay appear to specialize in one tactic and subsequently limit their overall distribution patterns to coincide with habitats that facilitate success using that foraging tactic. This study demonstrates how foraging behavior can be an ecological determinant of overall dolphin habitat use patterns and works to create spatial structure within a population due to consistent mapping of tactics onto environmental variation. These foraging specializations potentially impact the social and demographic patterns of this dolphin population. The possible evolutionary mechanisms behind this intraspecific variation, including resource limitation and social learning, are considered.

Fine‐scale population structure of bottlenose dolphins ( Tursiops truncatus ) in Tampa Bay, Florida - Kim W. Urian; Sue Hofmann; Randall S. Wells; Andrew J. Read (Marine Mammal Science, 2009)
Some populations of coastal bottlenose dolphins ( Tursiops truncatus ) comprise discrete communities, defined by patterns of social association and long‐term site fidelity. We tested the hypothesis that bottlenose dolphins in Tampa Bay, Florida, form a single community. The longitudinal study of dolphins in Sarasota Bay, adjacent to Tampa Bay, allowed us to ground‐truth the definition of community and test whether our approach was robust to small sample sizes of resightings. We conducted photo‐identification surveys in Tampa Bay during 1988–1993, and identified 102 dolphins with 10 or more sightings. We used hierarchical cluster analysis to examine the locations and association indices of these dolphins. We used analysis of variance (ANOVA) to test for differences in mean locations and determine whether mean coefficient of association (CoA) values within a community were higher than among communities. Dolphins in Tampa Bay clustered into five putative communities differing significantly in location and CoA values. Kernel estimates of the ranges of these five communities exhibited little overlap; some communities had no overlap at all. We conclude that five discrete communities of bottlenose dolphins exist in Tampa Bay and that such fine‐scale structure may be a common feature of bottlenose dolphin populations throughout the southeastern United States.

OBIS-SEAMAP: The World Data Center for Marine Mammal, Sea Bird, and Sea Turtle Distributions - Patrick Halpin; Andrew Read; Ei Fujioka; Ben Best; Ben Donnelly; Lucie Hazen; Connie Kot; Kim Urian; Erin LaBrecque; Andrew Dimatteo; Jesse Cleary; Caroline Good; et al. (Oceanography, 2009)

Erratum to: Population structure of short-beaked common dolphins (Delphinus delphis) in the North Atlantic Ocean as revealed by mitochondrial and nuclear genetic markers - Luca Mirimin; Andrew Westgate; Emer Rogan; Patricia Rosel; Andrew Read; Jamie Coughlan; Tom Cross (Marine Biology, 2009)

Population structure of short-beaked common dolphins (Delphinus delphis) in the North Atlantic Ocean as revealed by mitochondrial and nuclear genetic markers - Mirimin Luca; Westgate Andrew; Rogan Emer; Rosel Patricia; Read Andrew; Coughlan Jamie; Cross Tom (Marine Biology, 2009)

Stewart Scherer: A short guide to the human genome - Andrew P. Read (Human Genetics, 2009)

Stomach contents of mass‐stranded short‐finned pilot whales ( Globicephala macrorhynchus ) from North Carolina - Vanessa J. Mintzer; Damon P. Gannon; Nélio B. Barros; Andrew J. Read (Marine Mammal Science, 2008)
We examined the stomach contents of 27 short‐finned pilot whales ( Globicephala macrorhynchus) that mass stranded on the North Carolina coast on 15 January 2005. Eleven whales had prey parts in their forestomachs. We used frequency of occurrence and numerical abundance to assess the relative importance of prey. Brachioteuthis riisei (numerical abundance 28%), an oceanic species, was the most important cephalopod prey, but Taonius pavo (12%) and Histioteuthis reversa (9%) also represented a substantial part of the diet. A large number of otoliths belonging to the fish Scopelogadus beanii were present (25%). These results differ from reports of the stomach contents of short‐finned pilot whales from the Pacific coast in which neritic species dominate the diet. Our findings also suggest that there is a considerable difference between the diet of short‐ and long‐finned pilot whales ( Globicephala melas ) in the western North Atlantic. The latter feed predominantly on the long‐finned squid ( Loligo pealei ) whereas the former feed on deep‐water species. Our results indicate the whales fed primarily off the continental shelf prior to stranding.

BOOK REVIEW | The Unnatural History of the Sea - Andrew Read (Oceanography, 2008)

Saving the Vaquita: Immediate Action, Not More Data - ARMANDO JARAMILLO‐LEGORRETA; LORENZO ROJAS‐BRACHO; ROBERT L. BROWNELL; ANDREW J. READ; RANDALL R. REEVES; KATHERINE RALLS; BARBARA L. TAYLOR (Conservation Biology, 2007)

Detlev Ganten, Klaus Ruckpaul: Encyclopedic reference of genomics and proteomics in molecular medicine - Andrew Read (Human Genetics, 2007)

Reproduction in short-beaked common dolphins (Delphinus delphis) from the western North Atlantic - Andrew J. Westgate; Andrew J. Read (Marine Biology, 2007)

An eddy covariance mesonet to measure the effect of forest age on land–atmosphere exchange - MICHAEL L. GOULDEN; GREGORY C. WINSTON; ANDREW M. S. McMILLAN; MARCY E. LITVAK; EDWARD L. READ; ADRIAN V. ROCHA; J. ROB ELLIOT (Global Change Biology, 2006)
We deployed a mesonet of year‐round eddy covariance towers in boreal forest stands that last burned in ∼1850, ∼1930, 1964, 1981, 1989, 1998, and 2003 to understand how CO 2 exchange and evapotranspiration change during secondary succession. We used MODIS imagery to establish that the tower sites were representative of the patterns of secondary succession in the region, and Landsat images to show that the individual stands have changed over the last 22 years in ways that match the spatially derived trends. The eddy covariance towers were well matched, with similar equipment and programs, which maximized site‐to‐site precision and allowed us to operate the network in an efficient manner. The six oldest sites were fully operational for ∼90% of the growing season and ∼70% of the dormant season from 2001 or 2002 to 2004, with most of the missing data caused by low battery charge or bad signals from the sonic anemometers. The rates of midday growing‐season CO 2 uptake recovered to preburn levels within 4 years of fire. The seasonality of land–atmosphere exchange and growing‐season length changed markedly with stand age. The foliage in the younger stands (1989, 1998, and 2003 burns) was almost entirely deciduous, which resulted in comparatively short growing seasons that lasted ∼65 days. In contrast, the older stands (1850, 1930, 1964, and 1981) were mostly evergreen, which resulted in comparatively long growing seasons that lasted ∼130 days. The eddy covariance mesonet approach we describe could be used within the context of other ecological experimental designs such as controlled manipulations and gradient comparisons.

John C. Avise: The hope, hype and reality of genetic engineering (2004) - Andrew P. Read (Human Genetics, 2006)

Bycatch of Marine Mammals in U.S. and Global Fisheries - ANDREW J. READ; PHEBE DRINKER; SIMON NORTHRIDGE (Conservation Biology, 2006)
Fisheries bycatch poses a significant threat to many populations of marine mammals, but there are few published estimates of the magnitude of these catches. We estimated marine mammal bycatch in U.S. fisheries from 1990 to 1999 with data taken from the stock assessment reports required by the U.S. Marine Mammal Protection Act. The mean annual bycatch of marine mammals during this period was 6215 ± 448 (SE). Bycatch of cetaceans and pinnipeds occurred in similar numbers. Most cetacean (84%) and pinniped (98%) bycatch occurred in gill‐net fisheries. Marine mammal bycatch declined significantly over the decade, primarily because of a reduction in the bycatch of cetaceans. Total marine mammal bycatch was significantly lower after the implementation of take reduction measures in the latter half of the decade. We derived a crude first estimate of marine mammal bycatch in the world's fisheries by expanding U.S. bycatch with data on fleet composition from the Food and Agriculture Organization. The global bycatch of marine mammals is in the hundreds of thousands. Bycatch is likely to have significant demographic effects on many populations of marine mammals. Better data are urgently needed to fully understand the impact of these interactions.

RESONANCE AND DISSONANCE: SCIENCE, ETHICS, AND THE SONAR DEBATE - Damon P. Gannon; David W. Johnston; Andrew J. Read; Douglas P. Nowacek (Marine Mammal Science, 2004)

The effect of a pathogen epidemic on the genetic structure and reproductive strategy of the crustacean Daphnia magna - Suzanne E. Mitchell; Andrew F. Read; Tom J. Little (Ecology Letters, 2004)
Host–parasite coevolution is potentially of great importance in producing and maintaining biological diversity. However, there is a lack of evidence for parasites directly driving genetic change. We examined the impact of an epidemic of the bacterium Pasteuria ramosa on a natural population of the crustacean Daphnia magna through the use of molecular markers (allozymes) and laboratory experiments to determine the susceptibility of hosts collected during and after the epidemic. Some allozyme genotypes were more heavily infected than others in field samples, and the population genetic structure differed during and after the epidemic, consistent with a response to parasite‐mediated selection. Laboratory studies showed no evidence for the evolution of higher resistance, but did reveal an intriguing life‐history pattern: host genotypes that were more susceptible also showed a greater tendency to engage in sex. In light of this, we suggest a model of host–parasite dynamics that incorporates the cycles of sex and parthenogenesis that Daphnia undergo in the field.

David Bainbridge (Editor), The X in sex: how the X chromosome controls our lives - Andrew P. Read (Human Genetics, 2004)

REPRODUCTIVE SEASONALITY OF WESTERN ATLANTIC BOTTLENOSE DOLPHINS OFF NORTH CAROLINA, U.S.A. - Victoria G. Thayer; Andrew J. Read; Ari S. Friedlaender; David R. Colby; Aleta A. Hohn; William A. McLellan; D. Ann Pabst; Jennifer L. Dearolf; Nan I. Bowles; John R. Russell; Keith A. Rittmaster (Marine Mammal Science, 2003)
A bstract We describe reproductive seasonality of bottlenose dolphins in North Carolina (NC), U.S.A., using strandings data from the entire coast of NC and sighting data from Beaufort, NC and by estimating dates of birth of known females. We found a strong peak of neonate strandings in the spring (April‐May), and low levels of neonate strandings in the fall and winter. The distribution of neonate strandings was significantly different from a uniform distribution ( P K = 3.8). We found a unimodal distribution of 282 sightings of neonates with a diffuse peak in the summer. The temporal distribution of sightings of neonates departed significantly from a uniform distribution (P K = 5.1). Estimated birth dates of neonates from known females occurred in May ( n = 6) and June ( n = 4), with a single fall birth. These methods shed light on bottlenose reproductive patterns and underscore the value of using information from multiple types of data. Clarification of bottlenose dolphin reproductive patterns, such as the seasonality of birth, may enhance our understanding of the population structure of this species in the mid‐Atlantic region.

IMPROVING MANAGEMENT OF OVERLAPPING BOTTLENOSE DOLPHIN ECOTYPES THROUGH SPATIAL ANALYSIS AND GENETICS - Leigh G. Torres; Patricia E. Rosel; Caterina D'Agrosa; Andrew J. Read (Marine Mammal Science, 2003)
A bstract In the Northwest Atlantic the distribution of coastal bottlenose dolphins ( Tursiops truncatus ) overlaps with that of the offshore ecotype. We hypothesized that the distribution of the two ecotypes could be delineated by depth and/or distance from shore, facilitating their identification during surveys. We obtained 304 skin biopsy samples and identified each as either coastal or offshore using analysis of mitochondrial DNA. We then interpreted the spatial distribution of coastal and offshore forms using spatial analysis. Using a Classification and Regression Tree (CART) analysis, we found a statistically significant break in ecotype distribution at 34 km from shore. In waters beyond 34 km from shore and deeper than 34 m, all bottlenose dolphins were of the offshore ecotype. Within 7.5 km of shore, all 65 samples were of the coastal ecotype. Between these two areas only nine samples were collected, so the genetic composition of bottlenose dolphins in this area remains poorly known. To enhance our understanding of the spatial distribution of the two ecotypes, future research should obtain more biopsy samples in this zone. Nevertheless, our results indicate that a conservative abundance estimate for the coastal ecotype could be generated from surveys of bottlenose dolphins within 7.5 km of shore.

ABUNDANCE OF BOTTLENOSE DOLPHINS IN THE BAYS, SOUNDS, AND ESTUARIES OF NORTH CAROLINA - Andrew J. Read; Kim W. Urian; Ben Wilson; Danielle M. Waples (Marine Mammal Science, 2003)
A bstract We conducted a mark‐recapture survey of bottlenose dolphins Tursiops truncatus in the bays, sounds, and estuaries of North Carolina during July 2000, using photographic identification techniques. During this survey we took 7,682 photographs of dolphins and, of these, 3,457 images were of sufficient quality for analysis. We identified 306 dolphins from distinctive nicks and notches on their dorsal fins. Eighry‐six dolphins were photographed on more than one occasion during the course of the survey; one dolphin was photographed on four separate days. We then applied the results of our photographic analyses to several mark‐recapture models and examined potential violations of the assumptions of these models, including an unexpected correlation between photo quality and mark distinctiveness. Our analysis suggests that our results are robusr to possible violations of these assumptions. The resulting estimates were then scaled to account for the proportion (0.46) of unmarked dolphins in the population. Our best estimate of the number of dolphins present in the inshore waters of North Carolina during July 2000 is 1,033 with a 95% Confidence Interval of 860–1,266 (CV = 0.099). Most dolphins were found in the northern part of the study area, which includes the second largest estuarine system in the United States.

HABITAT SELECTION OF FORAGING BOTTLENOSE DOLPHINS IN RELATION TO BOAT DENSITY NEAR CLEARWATER, FLORIDA - Mark C. Allen; Andrew J. Read (Marine Mammal Science, 2000)

Status of Marine Mammals in the United States - Andrew J. Read; Paul R. Wade (Conservation Biology, 2000)
The 1994 amendments to the U.S. Marine Mammal Protection Act required, for the first time, an assessment of the status of every marine mammal stock in the United States. We draw conclusions about the status of marine mammals from assessments of 153 stocks conducted to meet the requirements of these amendments. We found important regional differences in the status of stocks. Most stocks in the Atlantic and Pacific experience human‐induced mortality (takes), primarily from gill‐net fisheries. The proportion of stocks with takes was lower in the Gulf of Mexico and Hawaii, areas with few gill‐net fisheries. Estimated takes exceeded removal limits for 29% of stocks in the Atlantic, 14% in the Pacific, 8% in Alaska, 7% in the Gulf of Mexico, and 0% in Hawaii. Twenty‐eight stocks are listed as threatened or endangered under the U.S. Endangered Species Act. Most, but not all, baleen whale stocks are recovering after cessation of commercial harvests. Many species of pelagic cetaceans, including beaked and sperm whales, are vulnerable to mortality in pelagic drift‐net fisheries. Most pinniped stocks experience takes, but none of these takes exceeds removal limits, and all pinniped stocks on mainland coasts of the United States are increasing in abundance. Quantitative data on trends in abundance are available for few cetacean stocks, emphasizing the difficulty of monitoring trends in these species. These stock assessments have greatly advanced our understanding of the status of marine mammals in the United States, but information gaps remain, particularly regarding stock structure and possible mortality in unmonitored fisheries.

D avid E dward G askin 1939–1998 - Andrew J. Read; Heather N. Koopman; Andrew J. Westgate (Marine Mammal Science, 1999)

HEMATOLOGY VALUES OF WILD HARBOR PORPOISES ( PHOCOENA PHOCOENA ) FROM THE BAY OF FUNDY, CANADA - Heather N. Koopman; Andrew J. Westgate; Andrew J. Read (Marine Mammal Science, 1999)
A bstract Clinical hematology values were determined for 29 harbor porpoises ( Phocoena phocoena ) released from herring weirs in the Bay of Fundy, Canada. Erythrocyte values exhibited narrow ranges, but there was a high degree of individual variability in counts of white blood cells. Total white cell counts ranged from 2.6 to 15.5 ± 10 9 /liter, with an overall mean of 6.5 ± 2.7 ± 10±/liter. There were significant differences among reproductive classes in mean values of total red blood cells, hematocrit (HCT), mean cell volume (MCV), mean cell hemoglobin (MCHC) and total monocyte count. Wild harbor porpoises had fewer white blood cells, lower relative total number of neutrophils and lymphocytes, and higher percentages of monocytes and eosinophils than reported in the literature for captive porpoises. Compared to published values for other odontocetes, the hemograms of harbor porpoises were most similar to those of Pacific white‐sided dolphins ( Lagenorhynchus acutus ). These hematology data represent a baseline from free‐ranging harbor porpoises that can be used as a reference for long‐term monitoring of the health of this population and as a tool for rehabilitation facilities.

MONITORING A REHABILITATED HARBOR PORPOISE USING SATELLITE TELEMETRY - Andrew J. Westgate; Andrew J. Read; Tara M. Cox; T. David Schofield; Brent R. Whitaker; Kurt E. Anderson (Marine Mammal Science, 1998)

Drugs and parasites: global experiments in life history evolution? - Arne Skorping; Andrew F. Read (Ecology Letters, 1998)
Recent work has shown that the evolution of Drosophila melanogaster resistance to attack by the parasitoid Asobara tabida is constrained by a trade‐off with larval competitive ability. However, there are two very important questions that need to be answered. First, is this a general cost, or is it parasitoid specific? Second, does a selected increase in immune response against one parasitoid species result in a correlated change in resistance to other parasitoid species? The answers to both questions will influence the coevolutionary dynamics of these species, and also may have a previously unconsidered, yet important, influence on community structure.

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)